Upaya Meningkatkan Kemampuan Guru Mengembangkan Sumber dan Media Belajar dengan Diskusi Model Think Pair and Share di SD Negeri 3 Glagahwangi Polanharjo Klaten Semester II Tahun Pelajaran 2017/2018 - Endang Sri Purwanti (JPI (Jurnal Pendidikan Indonesia): Jurnal Ilmiah Pendidikan, 2019)
The general objective of the research is to find out how the discussion of think pair and share models is implemented in order to increase the active involvement and ability of teachers in developing learning resources and media. This type of research is School Action Research (PTS). The research subjects were 8 teachers. Data collection techniques using questionnaires, assignments, documentation and observation. Data analysis techniques use data reduction, data presentation and conclusions. The results of the study concluded that: (1) Discussion of think pair and share models gave an opportunity for each discussion participant (teacher) to work alone or collaborate by exchanging ideas and experiences, so that the discussion participants (teachers) interact intensively. (2) Discussion of think pair and share models can increase the activity of discussion participants (teachers) during the activity process. From the beginning until the end of the activity, the teacher involved is actively involved in each stage of the activity. (3) Discussion of the think pair and share model can improve the ability of teachers to develop learning resources and media, after they have done dikdusi or exchanged ideas and experiences with fellow teachers.